Screening for pentachlorophenol-degrading bacterial candidates for bioaugmentation in anaerobic bioprocesses and development of pentachlorophenol-induced toxicity bioassay. - Lio, Ivan Zong Long. (2013)
Refractory organic compounds, e.g. pentachlorophenol (PCP), have been reported to inhibit